DEVELOPING COMMUNICATIVE SKILLS THROUGH EXTRA LINGUISTIC SOURCES - Turayeva Dilafruz Maxammadjonovna (PEDAGOGS, 2024)
Communication is an integral feature of human activities.It is pillar which maintains the structure of peaceful co-existance and mutual understanding.It can be described as the process of transmitting and receiving ideas, information and method. Communication is a process of sharing information through speech ,writing,gesture or symbols between two or more people.It is a vital aspect of our daily lives, and being able to express ourselves effectively is essential. Communicative skills are not limited to just language; there are various extra-linguistic tools that we can use to enhance our communication abilities. In this article, we will discuss how these tools can help us develop our communicative skills